SAFETY AND OUTCOME OF SAME DAY DISCHARGE VS OVER-NIGHT STAY AFTER ELECTIVE PCI IN PATIENTS WITH STABLE CAD: A RANDOMIZED CONTROL TRIAL IN ARMY CARDIAC CENTE - Malik, Muhammad Faheem Iqbal; Khan, Muhammad Nadir; Yusuf, Muhammad Tahir; Ahmad, Ayaz; Ahmed, Muhammad Shoaib; Danyal, Shoaib Muhammad (Pakistan Armed Forces Medical Journal, 2019)
Objective: To determine and compare the safety and outcomes of same day discharge patients with over-night stay patients after elective percutaneous coronary interventions with stable coronary artery disease. Study Design: Randomized controlled trial. Place and Duration of Study: This study was conducted at Army Cardiac Center, Lahore from, Jun 2017 to Jul 2018. Methodology: Hundred patients with stable CAD were recruited after their informed consent. Patients were randomized through lottery method using list of patients. Fifty patients were discharged on the same day of PCI while 50 patients stayed over-night. Inclusion Criteria was patients of either gender with age <75 years undergoing elective PCI with no acute decompensated CHF or shock, LVEF > 30%, Serum creatinine <1.5 mg/dl and no contrast allergy. While those excluded were with multi vessel disease, bifurcation disease or left main disease, saphenous vein graft or internal mammary disease, recent ACS, ≥3 stents or Femoral access. Immediate adverse cardiac and cerebral events were noted in the first 24 hours. The procedural result followed by a 6-hours observation period allowed adequate triage of patients to same-day discharge or to extended clinical observation. The one month clinical follow up was also done. Data was analyzed using SPSS 23. Confidentiality of data was maintained. Results: Mean age of the patients was 54 ± 3.8 years, 81 male patients while 19 female patients. Most common comorbidity was hypertension in 62 patients followed by diabetes in 43, dyslipidemia in 39 patients and current smokers 20 (20%). Haematoma formation [3 (6.0% vs 4 (8.0%); p=0.04], allergic reaction [5 (10.0% vs 6 (12.0%); p=0.50] and re- hospitalization for chest pain [5 (10.0% vs 2 (4.0%); p=0.50] were almost the same. No cardiac death, MI, Repeat PCI, urgent CABG, stroke, re-hospitalization for bleeding or non-cardiac death were observed in both groups. When patients were asked about their preference of discharge, 47 (47.0%) patients preferred for same day discharge, 22 (22.0%) for over-night stay while 31 (31.0%) preferred whatever their doctor considered best for them. Conclusion: Our study results yielded that same day discharge after elective PCI is a safe practice. Post-procedural outcomes are the same in same day group and over-night stay group. Same day discharge strategy is a cost effective approach and should be considered for the future.